Data Integrity in Global Clinical Trials: Discussions From Joint US Food and Drug Administration and UK Medicines and Healthcare Products Regulatory Agency Good Clinical Practice Workshop. Issue 5 (28th March 2020) - Khin, Ni A.; Francis, Gail; Mulinde, Jean; Grandinetti, Cheryl; Skeete, Rachel; Yu, Bei; Ayalew, Kassa; Cho, Seongeun‐Julia; Fisher, Andrew; Kleppinger, Cynthia; Ayala, Ruben; Bonapace, Charles; et al.
Abstract : Good Clinical Practice (GCP) is an international ethical and scientific quality standard for designing, conducting, recording, and reporting clinical trials. Regulatory agencies conduct GCP inspections to verify the integrity of data generated in clinical trials and to assure the protection of human research subjects, in addition to ensuring that clinical trials are conducted according to the applicable regulations. The first joint GCP workshop of the US Food and Drug Administration (FDA) Center for Drug Evaluation and Research (CDER) and the United Kingdom Medicines and Healthcare products Regulatory Agency (MHRA‐UK) was held in October 2018 and provided the agencies' perspectives on the importance of data quality management practices on data integrity. Regulatory perspectives on data blinding to minimize introduction of bias, and the role of audit trails in assessing data integrity in global clinical trials were discussed. This paper summarizes considerations of both agencies on these topics, along with case examples.